(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores the Role of the Financial Action Task Force (FATF) in Combating Money Laundering. The Financial Action Task Force (FATF) plays a pivotal role in the global fight against money laundering, terrorist financing, and the proliferation of weapons of mass destruction. Established in 1989 by the G7 nations, FATF’s primary function is to set international standards and promote effective measures to combat financial crimes. Central to its efforts are the FATF Recommendations—40 comprehensive guidelines designed to help countries develop robust nti-money laundering (AML) and counter-terrorist financing (CTF) frameworks. FATF’s responsibilities include setting these standards, evaluating member countries’ compliance through rigorous mutual evaluations, and providing guidance to ensure effective implementation. The mutual evaluation process assesses the adequacy and effectiveness of national AML/CTF systems, leading to public reports that highlight strengths, weaknesses, and areas for improvement. This process not only fosters accountability but also drives countries to address deficiencies and enhance their frameworks. Furthermore, FATF promotes international cooperation by encouraging information sharing, mutual legal assistance, and collaborative efforts among countries and international organizations. Its role extends to addressing emerging risks by updating standards and issuing thematic reports on new threats, such as the misuse of virtual assets. FATF’s influence is also evident in its listing and public statements, which identify jurisdictions with significant AML/CTF deficiencies and encourage global focus and corrective actions. Through these mechanisms, FATF contributes to a more transparent, accountable, and resilient global financial system, ensuring that countries are better equipped to prevent and respond to financial crimes and maintain the integrity of the international financial system.